The Influence of Motivation, Ability, Work Environment and Digital on Employee Performance - Cherly Elisabeth (Universitas Dharma Wacana, 2022)
This study aims to determine the current performance conditions of BTN Bank Employees, Makassar Syariah Branch Office with the title The Effect of Motivation, Ability, Work Environment and Digital on the Performance of BTN Bank Employees, Makassar Syariah Branch Office. The variables in this study are Motivation (X1), ability (X2), work environment (X3), Digital (X4), Performance (Y). The theory used in this research is Attribution theory. The sample of this study were 60 respondents. The type of research conducted in this study is quantitative using primary data. The data collection technique was carried out using a questionnaire. The population of this study were all employees of Bank BTN Makassar Syariah Branch Office. The technique used to determine the sample is to use the saturated sample technique. The data analysis method used is descriptive statistical analysis, normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple regression analysis test, R Square test, t statistical test, and F statistical test. The results of the study partially show that motivation, ability, work environment and digital have a positive and significant effect on the performance of employees of BTN Bank Makassar Syariah Branch Office. Then together all independent variables affect the performance of employees of BTN Bank Makassar Syariah Branch Office.